Risk Factors for Migration, Fracture, and Dislocation of Pancreatic Stents - Yoshiaki Kawaguchi; Jung-Chun Lin; Yohei Kawashima; Atsuko Maruno; Hiroyuki Ito; Masami Ogawa; Tetsuya Mine (Gastroenterology Research and Practice)
Aim. To analyze the risk factors for pancreatic stent migration, dislocation, and fracture in chronic pancreatitis patients with pancreatic strictures. Materials and Methods. Endoscopic stent placements (total 386 times) were performed in 99 chronic pancreatitis patients with pancreatic duct stenosis at our institution between April 2006 and June 2014. We retrospectively examined the frequency of stent migration, dislocation, and fracture and analyzed the patient factors and stent factors. We also investigated the retrieval methods for migrated and fractured stents and their success rates. Results. The frequencies of stent migration, dislocation, and fracture were 1.5% (5/396), 0.8% (3/396), and 1.2% (4/396), respectively. No significant differences in the rates of migration, dislocation, or fracture were noted on the patient factors (etiology, cases undergoing endoscopic pancreatic sphincterotomy, location of pancreatic duct stenosis, existence of pancreatic stone, and approach from the main or minor papilla) and stent factors (duration of stent placement, numbers of stent placements, stent shape, diameter, and length). Stent retrieval was successful in all cases of migration. In cases of fractured stents, retrieval was successful in 2 of 4 cases. Conclusion. Stent migration, fracture, and dislocation are relatively rare, but possible complications. A good understanding of retrieval techniques is necessary.